The relation between computational thinking and logical thinking in the context of robotics education - Veenman, Kim; Tolboom, Jos L. J.; van Beekum, Olivier (Frontiers in Education, 2022)
Computational thinking is a popular student skill on a steep rise today. Nevertheless, the assessment of this skill is a matter of contention. This pilot study examines whether computational and logical thinking are related. Therefore, we investigated the effect of a robotics course concerning logical thinking and computational thinking on 14-year-old Dutch students. Thirty-five students were pre-tested to assess their logical thinking and post-tested for their logical thinking and their computational thinking. The intervention group (N = 11) followed a robotics course between the pre- and post-test. This study's results show a significant positive correlation between computational and logical thinking. This study, with small sample size, does not show the effect of the robotics course on either logical or computational thinking.